Diagnosis of the chemical quality of wines produced in the southern region of Minas Gerais state, Brazil (Research, Society and Development, 2020)
The southern region of Minas Gerais state, Brazil, is traditionally a producer of table wines made from the grape varieties Bordô or Folha de Figo, Jacquez and Niágara; however, in recent years, this tradition has been forgotten, with some of the vineyards and wineries extinct. The current state of the art of the region's wines, diagnosed through physical-chemical analysis, needs to be known to understand the quality of the beverages and the observance of an eventual identity of the local products, which can contribute to obtaining a seal of indication of origin and strengthening of the region's wine tradition. To this, 30 samples of wines from the region were collected and submitted a several analysis: pH, total titratable acidity, volatile acidity, fixed acidity, ethanol, free sulfur dioxide, total sulfur dioxide, sulfates, dry extract, ash, phenolic compounds, anthocyanins, glucose, glycerol, tannins, reducing sugars, total reducing sugars, color intensity, and tonality. The results showed that there is a great difference in the composition of the analyzed wines, given the great variability of the samples, with wines produced from different grapes. Two samples showed ethanol values outside the limits established by Brazilian legislation. Three samples showed values of total acidity above the allowed and seven showed values of volatile acidity above the maximum limit established by law. The parameters of color intensity and hue, the only sensory characteristics analyzed, showed great variability of the values, accentuating the lack of standardization of the analyzed beverages. The results indicate that, in order to obtain a seal of geographic identity, there is a need to adapt some aspects of production.